2017
DOI: 10.1111/epi.13715
|View full text |Cite
|
Sign up to set email alerts
|

Laser thermal ablation for mesiotemporal epilepsy: Analysis of ablation volumes and trajectories

Abstract: Objective To identify features of ablations and trajectories that correlate with optimal seizure control and minimize the risk of neurocognitive deficits in patients undergoing laser interstitial thermal therapy (LiTT) for mesiotemporal epilepsy (mTLE). Methods Clinical and radiographic data were reviewed from a prospectively maintained database of all patients undergoing LiTT for the treatment of mTLE at the University of Miami Hospital. Standard pre- and post-operative evaluations, including contrast-enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
154
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(162 citation statements)
references
References 16 publications
(52 reference statements)
7
154
0
1
Order By: Relevance
“…In the most recently published study which was not included in the mini-review, class I outcome was achieved in 11 (73%) of 15 patients with MTS and in 5 (62%) of 8 patients without MTS. There was no statistical difference of class I outcome in patients with MTS and without MTS 25. When combining all the published cases including those in the current study, class I seizure outcome was achieved in 36 (67%) of 54 patients with MTS and 9 (38%) of 24 patients without MTS.…”
Section: Discussionmentioning
confidence: 47%
“…In the most recently published study which was not included in the mini-review, class I outcome was achieved in 11 (73%) of 15 patients with MTS and in 5 (62%) of 8 patients without MTS. There was no statistical difference of class I outcome in patients with MTS and without MTS 25. When combining all the published cases including those in the current study, class I seizure outcome was achieved in 36 (67%) of 54 patients with MTS and 9 (38%) of 24 patients without MTS.…”
Section: Discussionmentioning
confidence: 47%
“…The largest and most favorable experience is reported in Jermakowicz et al 6 In their series of 23 SLAH patients, 5 of 8 (63%) without MTS were seizurefree with a minimum 1-year follow-up. Use of intracranial depth electrodes to confirm seizure onset in this population is variable.…”
Section: Discussionmentioning
confidence: 97%
“…Patients unwilling to consider open surgery may be more amenable to a minimally invasive approach. Oneyear seizure freedom rates have been reported in fewer than 50 patients, [2][3][4][5][6]13 and it will be several years before the results of the Stereotactic Laser Ablation for Temporal Lobe Epilepsy (SLATE) trial-an ongoing, large prospective cohort study-are available. 3,5 Some have suggested that SLAH may be the preferable first-line surgical option for MTLE, with open surgery reserved for those with persistent seizures after one or more failed ablations.…”
Section: Introductionmentioning
confidence: 99%
“…LITT typically includes ablation of tissue anterior to the hippocampus, while the posterior margin is limited to avoid damaging optic radiations that might lead to visual field deficits. A recent report indicated that sparing of the medial parts of the hippocampal head significantly decreased the likelihood for good seizure outcome17; however, future research is needed to confirm this. Likewise, the ideal trajectories for mesial temporal ablation are unclear.…”
Section: Shortcomings and Future Directionsmentioning
confidence: 97%
“…Further analysis of ablations within this area in 23 patients found that the sparing of the medial hippocampal head was associated with significantly worse seizure outcome 17. This raises the question of whether, when a single trajectory approach is used, it should always be angled in such a way that ablation of the medial hippocampal head is accomplished.…”
Section: Technical Aspects (Mri-guided Thermal Imaging)mentioning
confidence: 99%